Faktor Yang Mempengaruhi Keputusan Pengunjung Berwisata ke Taman Safari Indonesia di Kabupaten Bogor Selama Pandemi Covid-19 - Sabila, Ainun; Sudiarta, I Nyoman; Sunarta, I Nyoman (Jurnal Master Pariwisata (JUMPA); Volume 09, Nomor 01, Juli 2022, 2022)
The occurrence of Covid-19 pandemic in Indonesia did not prevent the public's intention to travel. It can be seen because of the high their travel enthusiasm, especially to Puncak area and other tourist attraction of Taman Safari Indonesia (TSI) in Bogor. This study aims to: 1) analyze the factors which influence the decision of visitors to travel and 2) analyze the most dominant factors that can influence the decision of visitors to travel to TSI during the Covid-19 pandemic. The design of this research was exploratory research with a quantitative approach with 140 respondents from TSI visitors who were determined based on purposive sampling in this study. The analytical method used was factor analysis using SPSS software version 28 for windows. The results showed that, there were 5 (five) factors that influence the decision to visit TSI during the Covid-19. First factor was a tourist attraction, then followed by psychological as second factor, experience as third factor while awards and special events as fourth factor and fifth factor. The most dominant factor that influence the visitor's decision to travel to TSI during the Covid-19 was psychological as a push factor. Meanwhile the pulling factor was tourist attraction. The implication of this research was providing additional information related to push and pull factors that influence visitor behaviour in making travel decisions. The recommendations for further research were to be able to use more indicators that have not been used in this study such as playing, adventure, health, natural scenery, electronic word of mouth and others. So, it can provide various research for tourism field in the future. Keywords: covid-19 pandemic, travel motivation, push-pull factors, decision to visit, visitor, taman safari indonesia bogor.